Chemical composition and evaluation of the antimicrobial activity of the essential oil from leaves of Eugenia platysema. Issue 17 (1st September 2016) - Tenfen, Adrielli; Siebert, Diogo Alexandre; Yamanaka, Celina Noriko; Mendes de Córdova, Caio Maurício; Scharf, Dilamara Riva; Simionatto, Edésio Luiz; Alberton, Michele Debiasi
Abstract: This study describes the qualitative and quantitative chemical composition and evaluates the antibacterial activity of essential oil from Eugenia platysema leaves. Analysis by GC–FID and GC–MS allowed the identification of 22 compounds. Different from the other species of the Eugenia genus, the major compound found in the essential oil was the diterpene phytol (66.05%), being this the first report of the presence of this compound in the essential oils from Eugenia genus. The sesquiterpene elixene was the second most concentrated compound in the studied essential oil (9.16%). The essential oil from E. platysema was tested for its antibacterial activity against cell-walled bacteria and mollicute strains of clinical interest using the microdilution broth assay. The results showed that the essential oil of E. platysema was inactive until 1000 μg mL −1 against tested bacteria. Abstract :